Nanoparticle-Based Lateral Flow Biosensors Integrated With Loop-Mediated Isothermal Amplification for the Rapid and Visual Diagnosis of Hepatitis B Virus in Clinical Application - Chen, Xu; Wang, Shoshi; Tan, Yan; Huang, Junfei; Yang, Xingui; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatitis B virus (HBV) infection remains one of the major public health issues worldwide. Developing a rapid, sensitive, specific, easy-to-operate, and cost-saving approach for the diagnosis of HBV is essential for its therapy and prevention. Here, we first devised a novel approach, termed “loop-mediated isothermal amplification integrated with a nanoparticle-based lateral flow biosensor (LAMP-LFB),” for the detection of HBV in clinical application. The results indicated that a set of LAMP primers based on the S gene were valid for the establishment of HBV-LAMP-LFB. The optimal HBV-LAMP can be carried out at a constant temperature of 65°C for 40 min. The whole detection process, including HBV genomic DNA preparation (∼10 min), LAMP (40 min), and LFB reading (within 2 min), can be accomplished within 60 min. The limit of detection of the HBV-LAMP-LFB assay was 7.5 IU per test. The specificity of this assay was one hundred percent, and there was no cross-reactivity with other pathogens. Hence, these results indicated that the HBV-LAMP-LFB assay established in the current study is a sensitive, rapid, specific, visual, simple, and cost-saving method for the screening of HBV agents. More importantly, the HBV-LAMP-LFB has remarkable potential to develop a point-of-care testing in clinical application, especially in resource-scarce regions.